Urban sprawl, population density, and crime: an examination of contemporary migration trends and crime in suburban and rural neighborhoods - Battin, Joshua R. (Crime prevention and community safety, 2017)
This study examines the effects of urban sprawl and population density on crime in suburban and rural municipalities. It is posited that population density provides additional context to macro-level crime research, potentially impacting the vitality of neighborhoods’ social institutions. Three models were created using data from the 2000 and 2010 US Census and Uniform Crime Reports for 142 municipalities, measuring the effect of municipal characteristics and population density on violent and property crimes. The results reveal that the traditional neighborhood characteristics measured in social disorganization research provide significant explanatory power for both measures of crime at the municipal level. Population density was found to have a significant negative relationship with property crime. A discussion and future research suggestions are presented to conclude.